THE EFFECT OF SOCIAL MEDIA MARKETING ON AWARENESS AND BRAND IMAGE OF LOCAL FASHION THROUGH CONSUMER BRAND ENGAGEMENT - Reyvina, Reyvina; Tjokrosaputro, Miharni (International Journal of Application on Economics and Business, 2024)
This study aimed to determine whether Social media marketing affects a positive and significant role in awareness and brand image of local fashion through consumer brand engagement. This type of study is descriptive, and data collection is cross-sectional. A survey method was used in this study, and data were collected by questionnaire using a 5-point Likert scale. The data of this study were collected from 208 responses from Indonesians born between 1981 to 2012 who wear or ever have used local fashion brands using a probability sampling technique with convenience sampling method, and the data was then analyzed using smartPLS software version 3.2.8 by testing the outer model analysis and inner model analysis. This research is expected to fill research gaps on brand awareness and brand image through consumer brand engagement for local fashion brands in which local fashion brands face a challenge in creating and implementing social media marketing strategies that attract consumers. According to the findings of this study, social media marketing positively and significantly impacts local fashion brand awareness and brand image through consumer brand engagement. This research is thought to contribute to academics and practitioners about the Effect of Social media marketing through consumer brand engagement and their effects on awareness and brand image.